Evaluation of ROV-Based Coral Reef Monitoring System: A Comparative Analysis with Underwater Photo Transect in Nabire Waters, Cenderawasih Bay National Park, Indonesia - Nicodemus Rahanra; Abdul Hamid Toha; Paulus Boli; Selvi Tebay (PT. Hafasy Dwi Nawasena, 2026)
Background: Coral reef monitoring in tropical archipelago regions faces persistent challenges including limited diver availability, high operational costs, and safety risks. Remotely Operated Vehicles (ROV) have emerged as a promising technological alternative, yet systematic evaluation of their accuracy and efficiency relative to established quantitative methods remains limited, particularly in Indonesian waters. Methods: A parallel comparative survey was conducted on 6 January 2025 at Nusi Island, Cenderawasih Bay National Park, Nabire, Papua Province, Indonesia. Two stations (Nusi 1 and Nusi 2) were monitored simultaneously using Underwater Photo Transect (UPT) analysed with Coral Point Count with Excel extensions (CPCe) software and a Gladius Mini ROV (MORAL-BOT system). Each UPT station generated 1,500 random-point classifications from 50 photographic frames along a 50-m transect. Relative deviation analysis and descriptive statistics (Shapiro-Wilk, Mann-Whitney U, Cohen’s d effect size) were applied to compare methodological performance. Cost and time efficiency were assessed using activity-based costing and time-motion study. Results: UPT-CPCe detected live hard-coral cover (HC) of 29.89% at Nusi 1 (Moderate category) and 3.13% at Nusi 2 (Poor category), with a statistically significant difference (Mann-Whitney U, p < 0.05; Cohen’s d = 1.008, large effect size). ROV estimated HC < 5% at both stations. Mean relative deviation between methods was 87.8% at Nusi 1 (patchy habitat) and 13.1% at Nusi 2 (homogeneous degraded habitat). ROV surveys were completed 3.8× faster (55 min vs. 210 min) and at 83% lower operational cost (Rp 2,100,000 vs. Rp 12,500,000) compared with UPT. Conclusions: UPT-CPCe outperforms ROV in quantitative precision and taxonomic resolution, especially in heterogeneous reef habitats. Conversely, ROV provides significant advantages in operational efficiency, safety, and the ability to access greater depths. A hybrid monitoring protocol—ROV for rapid spatial coverage and UPT for quantitative baseline validation—is recommended as the optimal approach for large-scale, cost-effective reef monitoring in Indonesia’s eastern archipelago.